Retrospective observational analysis of a coronary artery bypass grafting surgery patient cohort: Off-pump versus on-pump - Rantanen Matias; Yousif Rizgar; Kallioinen Minna; Hynninen Ville-Veikko; Peltoniemi Marko; Söderholm Oki; Saarikoski Tuukka; Anttila Vesa; Aittokallio Jenni (Elsevier, 2022)
Objectives
To determine whether surgical technique has an effect on prognosis in coronary artery bypass grafting (CABG).
Design
Retrospective observational.
Setting
Single center.
Participants
All the off-pump (OPCABG) and on-pump (ONCABG) patients at Turku University Central Hospital in 2018.
Interventions
None.
Measurements and main results
After propensity score matching, perioperative, 1-year and 3-year mortality did not differ between the groups. The ONCABG patients received more allogenic red blood cells (1.3 vs. 0.6 units, p = 0.020), autologous red blood cells (564 vs. 285 ml, p < 0.001) and crystalloids (3388 vs. 2808 ml, p < 0.001), and had higher postoperative values of troponin T (581 vs. 222, p = 0.001) and lactate (1.69 vs. 1.23, p < 0.001) than the OPCABG patients.
Conclusions
The both techniques seem equally safe. However, there may be some benefits to avoiding using a heart-lung machine, such as lower infused fluid volumes. Myocardial damage may also be milder and postoperative hemodynamics more balanced in OPCABG patients, based on lower levels of troponin T and lactate.